Psychological Profiling of Criminals in Violent Crime Investigations in Nigerian Criminal Justice System - Adebisi, Kolawole Shittu; Olanrewaju, Daramola Nurudeen (International Journal of Criminology and Sociology, 2021)
The Nigerian criminal justice system is not entirely ignorant or unaware of the use and the merits of the application of criminal profiling as a tool in crime investigation. The technique was introduced to help law enforcement agencies solve serious crimes such as serial rape or murder and to a lesser extent arson and property crime. At the heart of profiling lies the belief that by combining psychological principles with crime scene analysis, it is possible to identify the likely characteristics of a perpetrator. However, criminal profiling in Nigeria has not nearly reached the level of recognition, functionality, or institutionalization that it has attained in other jurisdictions. This study aims to examine the feasibility and the practicality of offender profiling in a criminal investigation of violent crimes with a particular focus on the Nigerian criminal justice system. It will also give an expository critique of the loopholes and impediments in the Nigerian criminal justice system and ways criminal profiling can fill up these holes. The research methods employed in this study include a combination of both primary and secondary sources. The work highlighted the effectiveness of this field and thus concluded that criminal investigative analysis should be effectively immersed into the justice system and should also receive as much recognition as it has in other jurisdictions especially in the United States and in major parts of Europe.